1999
DOI: 10.1080/074811899200984
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Bereavement and Posttraumatic Stress Disorder Following Fatal Car Crashes: Recommendations for Death Notification Practice

Abstract: This article reviewed how four characteristics of car crash deaths--suddenness, untimeliness, preventability, and violent, mutilating injuries--may contribute to complicated bereavement syndromes or to the development of posttraumatic stress disorder (PTSD). The Fatality Analysis Reporting System was then used to assess the proportion of car crashes from 1990-1996 that involved one or more of these characteristics. At least 75% of all deaths involved suddenness, untimeliness, or were preventable, that is, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 40 publications
1
75
0
1
Order By: Relevance
“…Unlike the gradual demise of a relative with a progressive illness, bereavement by sudden and unanticipated violence robs the family of the innoculatory balm of anticipation. Added to this is the stark confrontation of the survivors with their own mortality and vulnerability as the illusion of safety and order in the world is shattered (Amick-McMullan et al, 1989;Armour, 2003;Bard & Sangry, 1986;Boss, 2002;Carson & MacLeod, 1997;Getzel & Masters, 1984;Janoff-Bulman, 1992;MacLeod, 1999;Miller, 1994Miller, , 1998aMiller, , 1998bMiller, , 1999Miller, , 2003aMiller, , 2003bMiller, , 2008Miller & Schlesinger, 2000;Niemeyer, 2000Niemeyer, , 2001Park & Folkman, 1997;Raphael, 1983;Ressler et al, 1988;Rynearson, 1984Rynearson, , 1988Rynearson, , 2001Rynearson & McCreery, 1993;Sewell, 1993Sewell, , 1994Sprang & McNeil, 1995;Sprang et al, 1989;Stewart, 1999;Worden, 1991).…”
Section: Effect Of a Loved One's Murder On Family Membersmentioning
confidence: 99%
“…Unlike the gradual demise of a relative with a progressive illness, bereavement by sudden and unanticipated violence robs the family of the innoculatory balm of anticipation. Added to this is the stark confrontation of the survivors with their own mortality and vulnerability as the illusion of safety and order in the world is shattered (Amick-McMullan et al, 1989;Armour, 2003;Bard & Sangry, 1986;Boss, 2002;Carson & MacLeod, 1997;Getzel & Masters, 1984;Janoff-Bulman, 1992;MacLeod, 1999;Miller, 1994Miller, , 1998aMiller, , 1998bMiller, , 1999Miller, , 2003aMiller, , 2003bMiller, , 2008Miller & Schlesinger, 2000;Niemeyer, 2000Niemeyer, , 2001Park & Folkman, 1997;Raphael, 1983;Ressler et al, 1988;Rynearson, 1984Rynearson, , 1988Rynearson, , 2001Rynearson & McCreery, 1993;Sewell, 1993Sewell, , 1994Sprang & McNeil, 1995;Sprang et al, 1989;Stewart, 1999;Worden, 1991).…”
Section: Effect Of a Loved One's Murder On Family Membersmentioning
confidence: 99%
“…First, these three kinds of death may occur suddenly, involve some degree of violence or mutilation before death, and be perceived by the survivors as deaths that were somehow preventable or avoidable ( Cleiren, 1993;Rando, 1993;Stewart, 1999 ). These characteristics, among others, may make the loss especially traumatic for the survivors when the noti cation occurs.…”
Section: Ifficult Losses and Survivor Reactionsmentioning
confidence: 99%
“…Performing an extremely difficult task such as death noti cation with no previous training can make a noti er feel helpless and powerless ( Bartone, Ursano, Wright, & Ingraham, 1989;Ender & Hermsen, 1996;Stewart, 1999 ). Education that helps noti ers to respond e¡ectively to particularly stressful situations can make the noti cation process less traumatic in the short term and ultimately may reduce professional burnout and job turnover.…”
Section: N Eeds For D Eath N Oti Cation Educationmentioning
confidence: 99%
“…[1][2][3] Death notification not only puts a toll on the informer performing the task, but may also have long-term effects on the grief process of survivors. 4 Despite the fact that this task is of central importance and has significant implications, less than half of physicians in one study "reported receiving any education during medical school or residency" in death notification, and 94% reported "a need for education in dealing with death and dying". 5 The task of learning death notification is complex.…”
Section: Introductionmentioning
confidence: 95%